Design and prediction hydrodynamic performance of horizontal axis micro-hydrokinetic river turbine. (April 2019) - Wang, Wen-Quan; Yin, Rui; Yan, Yan
Abstract: This paper developed a horizontal axis micro-hydrokinetic river turbine (HAMHRT) technology for local renewable energy applications. Firstly, a hydrofoil shape was selected, and the hydrodynamic and cavitation characteristics of the hydrofoils were analyzed, then the chord length and twist angle for different blade location were optimal, and finally a 2 m diameter with 3-bladed HAMHRT was designed. Then, the numerical computational model of a hydrodynamic analysis for the prototype HAMHRT was carried out to determine force distributions along the blade under normal and extreme operating conditions, including the non-designed conditions, different tip speed ratios as well as the different pitch angles. The rotor has a maximum efficiency of 25.2% at the river current speed of 0.8 m/s, pitch angle of 4° and TSR of 6. It is ensured that the rotor performance does not deteriorate in a relative large scope even if the current speed changes or if the TSR deviates from the design values. Finally, the unsteady behaviors of hydrodynamics of this HAMHRT were analyzed farther. From the output performance of this turbine, the designed rotor was found to have stable power output and good efficiency at current speeding conditions. Highlights: A horizontal axis micro-hydrokinetic river turbine (HAMHRT) is designed for a current speed of 0.8 m/s. A hydrofoil shape and size (chord length and twist angle) is selected and optimal. The steady characteristics of hydrofoils and HAMHRT were studied numerically. The unsteady hydrodynamics characteristics of the 3-bladed 2 m diameter rotor have studied numerically.